Variability in optical particle backscattering in contrasting bio-optical oceanic regimes - Antoine, David; Siegel, D.; Kostadinov, T.; Maritorena, S.; Nelson, N.; Gentili, B.; Vellucci, V.; Guillocheau, N. (American Society of Limnology and Oceanography, Inc., 2011)
Variability in the optical particle backscattering coefficient (bbp) is investigated in oceanic waters from two sites, namely the BOUée pour l’acquiSition d’une Série Optique à Long termE site in the northwestern Mediterranean Sea and the Plumes and Blooms stations in the Santa Barbara Channel off Southern California. Data from these two sites span two orders of magnitude in bbp and likely cover typical open ocean values. A significant relationship is found between bbp at wavelengths of 442 and 555 nm and chlorophyll concentration. However the large spread in this relationship makes chlorophyll a poor predictor of bbp. The relationship between bbp and the particulate beam attenuation coefficient at 660 nm is tighter for both sites, indicating covariability of the particle size ranges that determine both coefficients. A detailed study of the seasonal changes of the bbp vs. chlorophyll relationship reveals that this bio-optical relationship might be best described as a succession of distinct regimes with rapid transitions from one to another. The backscattering ratio (b˜bp; the ratio of bbp to total particulate scattering, bp) ranges from about 0.2% to 1.5%, which is similar to previously reported values. The relationship between b˜bp and chlorophyll was not significant, while values of the backscattering ratio varied spectrally.